BMS-927711 for the acute treatment of migraine: A double-blind, randomized, placebo controlled, dose-ranging trial. (February 2014) - Marcus, Ronald; Goadsby, Peter J; Dodick, David; Stock, David; Manos, George; Fischer, Tanya Z
Background: BMS-927711 is a potent, selective, competitive human calcitonin gene-related peptide (CGRP) receptor antagonist that has shown in vivo efficacy without vasoconstrictor effect. The objective of the current study was to determine an effective and tolerable dose range of BMS-927711 for the acute treatment of migraine. Methods: In this randomized, double-blind, placebo controlled, dose-ranging study, 885 patients were randomized using an adaptive design to one of the following dose groups: BMS-927711 (10, 25, 75, 150, 300, or 600 mg); sumatriptan 100 mg (active comparator); and placebo. Patients were treated for a single migraine attack. The primary endpoint was pain freedom at two hours post-dose. Results: Of patients who took the study drug, 799 had one post-randomization efficacy evaluation. Significantly more patients in the BMS-927711 75 mg (31.4%, p = 0.002), 150 mg (32.9%, p < 0.001), and 300 mg (29.7%, p = 0.002) groups and the sumatriptan group (35%, p < 0.001) had pain freedom at two hours post-dose versus placebo (15.3%). For the secondary endpoint of sustained pain freedom from two to 24 hours post-dose, BMS-927711 doses (25–600 mg) were also statistically significant compared with placebo. No deaths or treatment-related serious adverse events (AEs) were reported, and no patients discontinued because of AEs. Conclusions: BMS-927711 is superior to placebo at several different doses (75 mg, 150 mg, and 300 mg) and has an excellent tolerability profile.